Nonalcoholic fatty liver disease is specifically related to the risk of hepatocellular cancer but not extrahepatic malignancies - Albhaisi, Somaya; McClish, Donna; Kang, Le; Gal, Tamas; Sanyal, Arun J. (Frontiers in Endocrinology, 2022)
Objective We performed a matched cohort study among individuals with and without nonalcoholic fatty liver disease (NAFLD) to determine: 1) the incidence of cancers (extrahepatic and liver) and their spectrum and 2) if NAFLD increases the risk of extrahepatic cancers. Methods The NAFLD and non-NAFLD (control) cohorts were identified from electronic medical records via International Classification of Diseases (ICD) codes from a single center and followed from 2010 to 2019. Cohorts were matched 1:2 for age, sex, race, body mass index (BMI), and type 2 diabetes. Results A total of 1,412 subjects were included in the analyses. There were 477 individuals with NAFLD and 935 controls (median age, 52 years; women, 54%; white vs. black: 59% vs. 38%; median BMI, 30.4 kg/m2; type 2 diabetes, 34%). The cancer incidence (per 100,000 person-years) was 535 vs. 1,513 (NAFLD vs. control). Liver cancer incidence (per 100,000 person-years) was 89 in the NAFLD group vs. 0 in the control group, whereas the incidence of malignancy was higher across other types of cancer in the control group vs. in the NAFLD group. Conclusions The overall extrahepatic cancer risk in NAFLD is not increased above and beyond the risk from background risk factors such as age, race, sex, BMI, and type 2 diabetes.